Nitrification Inhibition Using Benzotriazoles - T. Callender; L. C. Davis (Journal of Hazardous Substance Research, 2003)
The common corrosion inhibitor, 1H-benzotriazole (Bz), found as a component of glycol-based aircraft deicers, and its derivatives, such as 5-chloro-1H-benzotriazole (CBz), 1-hydroxybenzotriazole (HBz), and 5-methyl-1H-benzotriazole (MBz), are all potential nitrification inhibitors (McCarty and Bremner, 1989). The inhibitory effect of benzotriazoles on the nitrification of urea-N fertilizer in agricultural soils was examined over a four-week period. At 10 mg/kg, all compounds tested, except HBz, have the ability to inhibit the nitrification of urea-N fertilizer effectively. Their inhibitory capabilities depend on the structural components of the soil, particularly organic matter (O.M.). In the soil with the largest percent of O.M. (2.3%), inhibition by all the benzotriazole derivatives was considerably decreased. In the soil with least O.M. (0.3%), even HBz, the poorest of the inhibitors, showed signs of inhibition. For Bz, MBz, and CBz in the range of 90%, inhibition was observed in the soil with the lowest O.M. content during a four-week treatment period. On a mass basis Bz had the greatest inhibitory effect followed by MBz and CBz, whereas HBz showed little inhibition of the nitrification of urea-N in soils with >0.5% O.M. On a molar concentration basis, there would be little variation in inhibitory potency for MBz, CBz, and Bz. It was concluded that all three are effective nitrification inhibitors with urea-N fertilizer. Incorporation of benzotriazoles as inhibitors could help economize N fertilizers by helping prevent nitrate leaching and denitrification. However, the environmental fate of these compounds has not been determined, and they are toxic to plants and other organisms at higher concentrations (10-100 mg/L). Inhibition of nitrification is undesirable when high levels of ammonia are to be removed by combined nitrification and denitrification, as occurs in some sewage treatment processes.
Keywords: nitrification; benzotriazoles; deicing fluids; corrosion inhibitors; methylbenzotriazole; ADFs